Zmiany w systemach pracy implikowane rozwojem techniki i technologii - Jasiński, Zdzisław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The article shows the changes taking place in technical aspects of work systems. It presents their economic, organizational, and social results. It points to the need for change of manager's behaviour in modern work systems. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 305-309